Prognostic value of H3K27me3 in children with ependymoma. Issue 3 (18th December 2019) - Han, Zhe; Kang, Peng; Zhang, Heng; Liao, Zhiyi; Li, Chunde; Gong, Jian; Liu, Wei; Tian, Yongji
Abstract: Objective: To investigate the expression of H3K27me3 in different anatomical sites and analyze its prognostic value in children with ependymoma. Methods: A total of 188 children diagnosed with ependymoma were admitted to the Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, between 2012 and 2017, and regular follow‐up was conducted. Expression of H3K27me3 was analyzed by immunohistochemistry and scored semiquantitatively. The prognostic correlation was analyzed by Kaplan‐Meier and Cox regression survival analyses. Results: Of the 188 children with ependymoma, 61.7% were male, and the median and average age was five years (0‐17 years) and 6.26 years, respectively. There were 65 cases of supratentorial ependymoma, 115 cases of infratentorial ependymoma, and 8 cases of spinal cord ependymoma. The median follow‐up time was 39.95 months (0.3‐90.19 months). Five‐year progression‐free survival (PFS) and overall survival (OS) were 48.5% and 61.4%, respectively. Kaplan‐Meier univariate survival analysis showed that H3K27me3 expression had significant effects on PFS ( P = 0.0003) and OS ( P < 0.0001) in infratentorial ependymoma, but only affected OS ( P = 0.03) in supratentorial ependymoma. Conclusion: In Chinese children, infratentorial ependymoma with incomplete resection and no adjuvant radiotherapy is associated with poor OS. On the other hand, low expression of H3K27me3 indicates poor prognosis of infratentorial ependymoma, but it has no significant prognostic value for supratentorial ependymoma. In addition, high expression of H3K27me3 in spinal ependymoma may indicate a better prognosis.